Efektivitas Pelaksanaan Program Pupuk Bersubsidi pada Petani Padi Desa Tinggar Kecamatan Kadugede Kabupaten Kuningan Jawa Barat - Ghassani, Ratu; Supyandi, Dika (Universitas Galuh, 2024)
Subsidized fertilizer is a government assistance program aimed at helping farmers reduce the costs associated with purchasing fertilizer. However, implementation issues have arisen, as experienced in Tinggar Village, Kadugede District, Kuningan Regency, West Java. Farmers have complained about delays in fertilizer delivery and insufficient quantities. Therefore, this study was conducted to measure the effectiveness of the subsidized fertilizer program in Tinggar Village. The effectiveness can be measured using the 6T criteria: the right type, the right amount, the right price, the right place, the right time, and the right quality. This research uses a quantitative method, was using interviews and questionnaires distributed to 63 rice farmers receiving subsidized fertilizer. The collected data were analyzed using descriptive analysis and processed using an effectiveness measurement formula in percentage form. The results were then classified according to the effectiveness indicator categories. The study's findings that the effectiveness of the subsidized fertilizer program in Tinggar Village is categorized as quite effective.